The Learning Strategies for Beginning Reading in Class 1 Primary School - Sulastri, Tati; Syaodih, Ernawulan (International Conference on Elementary Education, 2024)
Early reading is a reading skill for children aged 5-6 years starting with recognizing letters or letter sounds, including vowels and consonants, then children learn to read words as a unit and focus more on the pictures around them, at this stage children begin to understand the meaning of words. The goal of beginning reading at the lower grade level is to give students the ability to read simple words and sentences fluently and accurately. The ability to read fluently and precisely at this stage is influenced by the activeness and creativity of teachers who teach in lower grades. In other words, teachers have a strategic role in improving students' reading skills. This research aims to describe the factors inhibiting students from beginning reading and determine the teacher's efforts in overcoming students' difficulties in beginning reading. Data collection techniques in this research are interviews and observation. This research uses a descriptive qualitative approach. The subject of this research was 1 grade 1 elementary school teacher. The results of this research show that teachers have used various strategies in beginning reading learning, including using the alphabet method, sound method, syllable method, and SAS method. Based on the results of this research, good cooperation between teachers and parents is needed to ensure that initial reading learning runs smoothly. Parents and teachers need to regularly provide stimulation to train children's early reading skills, both at home and at school